Love and a little white lie [large type] - Gray, Tammy L. (State of Grace, 2021)
"After a heartbreak leaves her reeling, January Sanders is open to anything -- including moving into a cabin on her aunt's wedding-venue property and accepting a temporary position at her aunt's church despite being a lifelong skeptic of faith. Choosing to keep her doubts to herself, she's determined to give her all to supporting Grace Community's overworked staff while helping herself move on. What she doesn't count on is meeting the church's handsome and charming guitarist. It's a match set for disaster, and yet January has no ability to stay away, even if it means pretending to have faith in a God she doesn't believe in. Only this time, keeping her secret isn't as easy as she thought it would be. Especially when she's constantly running into her aunt's landscape architect, who seems to know everything about her past-and-present sins and makes no apologies about pushing her to deal with feelings she'd rather keep buried. Torn between two worlds that can't coexist, can January find the healing that's eluded her, or will her resistance to the truth ruin any chance of happiness?"--